Islamic Bioethics Construction - Farhan Abdul Rahman, Muhammad; Rofiah, Nur; Nurbaiti, Nurbaiti (Journal of Comprehensive Science, 2025)
Islamic bioethics is a concept of medical ethics based on Islamic values, aiming to balance rights, responsibilities, and morality in medical practice. This concept is rooted in the role of humans as khalifah (stewards) on earth and the principles of maqasid al-shari‘ah, which include the protection of religion, life, intellect, lineage, and property. From an Islamic perspective, modern bioethical principles such as autonomy (patient autonomy), beneficence (doing good), non-maleficence (avoiding harm), and justice remain relevant but are contextualized within the framework of Islamic law. This study adapts modern bioethical principles and harmonizes them with Islamic teachings, forming the construction of Islamic Bioethics, which consists of four main pillars: jalb al-mashâlih (promoting benefits), dar‘u al-mafâsid (preventing harm), amanah (trust), and al-‘adl (justice), with ikhtiar (effort) as the overarching principle guiding the pursuit of healing. This approach emphasizes that medical efforts in Islam are not merely professional obligations but also acts of worship and ethical responsibility. Thus, this framework offers a bioethical paradigm that considers not only scientific and legal aspects but also the spiritual and moral dimensions in accordance with Islamic teachings.